O léxico da apicultura e da melinponicultura no Brasil: limites e flexibilidade para sua fixação em um dicionário terminológico - Peruchi, Rosane Malusá Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The relationship between man and bees dates from ancient times. In Brazil, it initially consisted of predatory extraction of honey from stingless bees and later of the introduction of bees of the genus Apis. Scientific interest concerning bees began with a search for ways to safely manage these bees and increase honey production. Currently, bee research has focused on examining the impact of these pollinating insects from socio-economic and environmental perspectives. Knowledge concerning the biology, conservation and rearing of the various species of bees directly affects environmental resilience and food security. Scientific knowledge is the key, and its dissemination is the door to access to knowledge and to the mobilization of society to protect biodiversity and prioritize sustainable agricultural production. This thesis, concerning specialized lexicography, seeks to contribute to knowledge about bees, through organization and dissemination of the terminology of this specific domain of human knowledge. It is a theoretical-methodological reflection directed towards the elaboration of a terminological dictionary. Divided into five parts, the thesis discusses the metalanguage necessary for lexicographic studies and comprehension of words as units of significance, learning and transmission of knowledge. The results include the corpus APIMELI - digital text base constituted based on Corpus linguistic principals; the facilities and limits of computational tools used for automatic extraction of vocabulary terms; the macrostructure of a dictionary with 2404 entries recorded in alphabetical order; and a pilot grouping with 225 entries of units that initiate with the letter M as an infrastructure model. This thesis conceives a terminological dictionary as a lexicographic product of semasiological orientation, to bring together a lexical collection, resulting from the linguistic interchange of specialist speakers, and a model for description ...

A relação entre homens e abelhas é histórica. No Brasil, ela é inicialmente marcada pelo extrativismo predatório de mel de melipon“neos e, posteriormente, pela introdução no pa“s de abelhas do gênero Apis. O interesse cient“fico pelas abelhas nasce com a busca de conhecimento para o manejo seguro dessas abelhas e o aumento da produtividade de mel. Atualmente, as pesquisas com abelhas (Apis e melipon“neos) visam mensurar o impacto desses insetos polinizadores sob a perspectiva socioeconômica e ambiental. O conhecimento, a conservação e a criação das diferentes espécies de abelhas estão diretamente relacionados à recuperação da resiliência ambiental e à segurança alimentar. A ciência é a chave, e sua divulgação, as portas de acesso ao conhecimento e à mobilização da sociedade na direção da preservação da biodiversidade e da produção agr“cola sustentável. Esta tese na área da Lexicografia Especializada oferece-se como uma contribuição, como possibilidade de organização e divulgação da terminologia desse dom“nio espec“fico do conhecimento humano. Trata-se de reflexão teórico-metodológica para a elaboração de um dicionário terminológico. Dividida em cinco seções, a tese discute a metalinguagem necessária ao trabalho lexicográfico e a compreensão da palavra como unidade de significação, aprendizagem e transmissão de conhecimento. Como resultados, apresentam-se o corpus APIMELI - base textual digital constitu“da a partir dos princ“pios da Lingu“stica de Corpus; as facilidades e os limites das ferramentas computacionais utilizadas para a extração automática do vocabulário terminológico; a macroestrutura do dicionário com 2404 entradas registradas em ordem alfabética; e, finalmente, um conjunto-piloto com 225 verbetes referentes às unidades iniciadas com a letra M como modelo de microestrutura. Esta tese concebe o dicionário terminológico como produto lexicográfico ...
Lexicon of brazilian apiculture and meliponiculture: limits and flexibility for its inclusion in a terminological
Keywords: Lexicografia; Abelha - Criação - Terminologia; Enciclopédias e dicionários; Lexicography